Systematic echocardiographic assessment of aortic regurgitation—what should the surgeon know for aortic valve repair? - Berrebi, Alain; Monin, Jean-Luc; Lansac, Emmanuel (Annals of Cardiothoracic Surgery; Vol 8, No 3 (May 01, 2019): Advanced Techniques in Aortic Valve Repair, 2019)
Aortic valve (AV) repair is the preferred surgical treatment in young patients with aortic regurgitation (AR) and/or proximal aorta aneurysm, as noted in the recent European Society of Cardiology (ESC) guidelines. However, this surgical option is still underused in clinical practice. This emphasizes the need to build a heart team dedicated to AV repair with expert surgeons and echocardiographers. Surgical techniques are now standardized in their approaches to enhance the reproducibility and expansion of AV repair. The objective of this keynote is to also demonstrate the need for a standardized pre-pump intra-operative echocardiography protocol to fulfill surgeon’s needs in providing a road map and predicting techniques to be used for an effective and durable repair.